Feasibility Study on Automatic Irrigation Scheme on the Jos Plateau Using Wind Power - Daniel, Samson; Aliyu, Hassan; Mamman, Buhari; Musa, Yarima Sa’id; Danladi, Muhammad Nazif (Darul Yasin Al Sys, 2025)
The over-dependence on rainfall agriculture is affecting crop production in Nigeria today, reducing crop yield and keeping farm output below demand. Irrigation farming is insurance for rain-fed agriculture even during the rainy season. The target site is Jos, Plateau state, with wind speed potential of 3ms-1 to 9.37ms-1 all year round, making it viable to generate power for pumping irrigation water. And also, the nature of the terrain which will enable or support the pump hydro storage technology. In this work, the focus is on the feasibility of a wind-powered pump hydro storage scheme for smart irrigation systems. This provided weekly irrigation water. The wind turbine farm can generate electric sufficient power to pump water from a lower reservoir to a higher head reservoir and also charge a batstery bank. At the time of irrigation, water is released from the higher reservoir through a series of control valves installed in the farm. The battery storage was used as a power source for the irrigation control system which uses the microcontroller to monitor and control the farm parameters using soil moisture sensors, a water level sensor for the upper reservoir, and the outlet valve. This system is expected to be fully automatic. The raw wind data collected was upgraded from 10m to a hub height of 50m to improve power generation. The wind turbine (S3-1000-B8) generates power to pump the minimum amount of water of 8.7m3 and a maximum of 176m3 per week. The power generated from the wind by this turbine was determined using polynomial regression which makes it suitable for this work. Twenty (S3-1000-B8) wind turbines were used to supply 180m3 of irrigation water required per week to irrigate 10,000m2 of farmland. For a one-month safe irrigation period, 720m3 of storage water is needed. From the wind potential, a single wind turbine can generate an average energy of 16kWh in a month and pump 234.864m3 of water. Therefore, in total the wind form will generate 336kWh and pump equivalent of 4,932m3.